Electrochemistry Test Strip as Platform for In Situ Detection of Blood Levels of Antipsychotic Clozapine in Finger-Pricked Sample Volume - Mehmet Senel (Biosensors, 2023)
With the increasing number of patients suffering from Parkinson’s disease, the importance of measuring drug levels in patient body fluids has increased exponentially, particularly for the drug clozapine. There is a growing demand for real-time analysis of biofluids on a single low-cost platform in ultra-low fluid volumes with robustness. This study aims to measure the level of clozapine (Clz) with a portable potentiostat using a practical approach. For this purpose, we developed an inexpensive, portable platform via electrochemistry on a commercial glucose test strip (CTS). CTSs were first modified by removing the enzyme mixture from the surface of the sensing zone, which was followed by modification with Multi walled carbon nanotube (MWCNT) and Nafion. The electrochemical characteristics of CTS electrodes were investigated using cyclic voltammetry (CV) and differential voltammetry (DPV) techniques. The designed sensor displayed decent linear range, detection limit, reproducibility, and reusability results. A linear dynamic range of 0.1–5 μM clozapine was observed under optimized conditions with a good sensitivity (1.295 μA/μM) and detection limit (83 nM). Furthermore, the designed sensing electrode was used to measure the amount of Clz in real samples.